Radikalisme Islam: Pergulatan Ideologi ke Aksi - Sefriyono Sefriyono; Mukhibat Mukhibat (IAIN Ponorogo, 2017)
Abstract: The violent actors in Islam known as terrorists ideologically always associated with kalam school which is called Khawarij. They are the fist ortodhox takfiri in Islam and their motto is who did not punish with His law, they were among those unbeliver. This paper with the critical history discusses the religious movement that often called activism with prevalently conflict, the radical movement in islam. Religous social movement can be interpreted with collective awarness who rise up their community for some value, a norm, and social practices in society during a certain period considered to be unfair and oppressive. The movement of the islamic activism in frame of social movement can be understood as fight with mobilization to support interest and the purpose of muslims. Based on the analysis of structure of islamic activism, the study on islamic activism is generally located on three large of domain, i.e. violence and contention, networks and alliance, and culture and framing.الملخص: إن القائمين بعملية العنف في الإسلام المسمّين بالإرهابيّين كانوا يرجعون عقائديّا إلى المذهب في علم الكلام )الخوارج(، الفرقة الأولى .» من لم يحكم بما أنزل الله فهو من الكافرين « للمذهب التكفيري بشعار حاولت هذه المقالة – بالمدخل النقدي التاريخي – دراسة الحركات الدينية أي حركات العنف في الإسلام. إن الحركات الدينية الإجتماعية يمكن أن يُفهم بوجود الوعي الجماعي الناشئ في نفوس المجتمع تجاه القيم و المعايير والعمليّات الإجتماعية الضالّة غير العادلة في مجتمع من المجتمعات في فترات معيّنة. وإن الحركات الإسلامية في ضوء الحركات الاجتماعية يمكن أن يكون له معنى تحريك روح العداوة لدعم فوائد وأهداف الأمة الإسلامية. واعتمادا على التحليل المؤسس على تنظيم الحركة الإسلامية، ة الحركات الإسلامية تقع في ثلات نقاط كبيرة: 1( العنف ???????? إن دراس والعداوة، 2( الشبكات والصلات، 3( الثقافة و الصياغة.Abstrak: Para pelaku kekerasan dalam Islam yang dikenal dengan teroris, secara ideolgis selalu dirujuk kepada aliran Kalam dalam Islam yang disebut dengan Khawarij sebagai kelompok takfiri ortodoks pertama dalam Islam dengan motto-nya siapa yang tidak berhukum dengan hukum Allah, mereka itu di golongkan kepada orang-orang kafir. Makalah ini dengan pendekatan kritis-historis mengkaji gerakan keagamaan yang sering disebut aktivisme Islam dalam kelaziman konfliktual yakni gerakan radikal dalam Islam. Gerakan sosial keagamaan dapat dimaknai dengan adanya kesadaran kolektif yang bangkit dalam diri masyarakat terhadap beberapa nilai, norma, dan praktek-praktek sosial di sebuah masyarakat pada periode tertentu yang dianggab tidak adil, menindas. Gerakan sosial/Aktivisme Islam dalam bingkai gerakan sosial bisa dimaknai dengan mobilisasi perseteruan untuk mendukung kepentingan dan tujuan kaum Muslimin. Berdasarkan analisis dengan struktur aktivisme Islam (Structur of Islamic Activisme), kajian terhadap aktivisme Islam umumnya berada pada tiga domain besar yakni, kekerasan dan perseteruan (violence and contention), jariangan dan aliansi (networks and alliances), dan kebudayaan dan pembingkaian (Culture and Framing).